Reimagining Athlete Development in Africa: A Multi-Sectoral Approach to Enhance Global Sporting Competitiveness (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Athlete scouting and development are critical pillars in the construction of a sustainable sports ecosystem. In Africa, where a vast youth population presents significant potential, the lack of structured and equitable scouting systems remains a major barrier to global competitiveness. This paper explores strategic frameworks for athlete identification, nurturing, and progression from grassroots to elite levels. It proposes a comprehensive, inclusive, and technology-driven scouting and development model tailored to the continent’s socio-economic realities and global sporting aspirations. Drawing from case studies and global best practices, the study advocates for integrating athlete development into educational curricula, strengthening community-based programs, and building talent pathways that connect schools, clubs, federations, and national teams. It emphasizes the role of sports science, digital platforms, and multidisciplinary support systems in enhancing long-term athlete performance and welfare. The study concludes by calling for policy innovation and intersectoral partnerships to maximize Africa’s athletic potential in an increasingly competitive global sports landscape.Mobile-based and cloud-enabled platforms represent feasible technological entry points for African contexts. Phased implementation aligned with funding capacity, coach education, and digital literacy is recommended.